2013
DOI: 10.1371/journal.pone.0084932
|View full text |Cite
|
Sign up to set email alerts
|

Strontium-Doped Calcium Phosphate and Hydroxyapatite Granules Promote Different Inflammatory and Bone Remodelling Responses in Normal and Ovariectomised Rats

Abstract: The healing of bone defects may be hindered by systemic conditions such as osteoporosis. Calcium phosphates, with or without ion substitutions, may provide advantages for bone augmentation. However, the mechanism of bone formation with these materials is unclear. The aim of this study was to evaluate the healing process in bone defects implanted with hydroxyapatite (HA) or strontium-doped calcium phosphate (SCP) granules, in non-ovariectomised (non-OVX) and ovariectomised (OVX) rats. After 0 (baseline), six an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 48 publications
(49 reference statements)
2
43
0
4
Order By: Relevance
“…Systemic administration of Sr (in the form of Sr ranelate-SrR) has been shown to improve bone quality and reduces the risk of fractures both in females with postmenopausal osteoporosis and osteoporotic men [17,18]. More recently, several experimental studies have shown promising results in terms of increased bone formation after Sr enrichment of various bone substitute materials, such as allogeneic bone [19], bioactive bioglass [20,21], calciumsilicon ceramic [22], calcium phosphate [23,24], and hydroxyapatite [25,26]. Furthermore, it was observed in recent experiments that Sr-loaded titanium implants presented significantly increased bone-to-implant contact, comparing to control implants [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic administration of Sr (in the form of Sr ranelate-SrR) has been shown to improve bone quality and reduces the risk of fractures both in females with postmenopausal osteoporosis and osteoporotic men [17,18]. More recently, several experimental studies have shown promising results in terms of increased bone formation after Sr enrichment of various bone substitute materials, such as allogeneic bone [19], bioactive bioglass [20,21], calciumsilicon ceramic [22], calcium phosphate [23,24], and hydroxyapatite [25,26]. Furthermore, it was observed in recent experiments that Sr-loaded titanium implants presented significantly increased bone-to-implant contact, comparing to control implants [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is supported by recent results showing that CaP materials doped with strontium, an osteoclastic inhibitor, induced a higher amount of bone formation than CaP materials. 41,42 This was associated with a significant reduction of the osteoclastic gene expression of CatK and CTR, whereas the osteogenic gene expression of ALP and OC was not affected. 41,42 Nevertheless, further evidence is required on the role of controlled nanotopography on the osteoclastic resorption, for instance by exploring the effect on the RANKL/RANK/OPG triad.…”
mentioning
confidence: 99%
“…41,42 This was associated with a significant reduction of the osteoclastic gene expression of CatK and CTR, whereas the osteogenic gene expression of ALP and OC was not affected. 41,42 Nevertheless, further evidence is required on the role of controlled nanotopography on the osteoclastic resorption, for instance by exploring the effect on the RANKL/RANK/OPG triad. Generally, few studies are available on the effect of nanotopography on osteoclasts, and contradictory findings to present observations have been reported showing that ceramics with less than 100 nm nanoscale grains and titanium implants with 70 nm TiO 2 nanotubes enhance the osteoclastic tartrateresistant acid phosphatase activity in vitro 43 and in vivo, 40 respectively.…”
mentioning
confidence: 99%
“…silicon [121,122], zinc [123][124][125][126], strontium [122,127,128]) into synthetic bioceramics and improved biological performance was observed both in vitro and in vivo (e.g. silicon [49,121,129], zinc [39,[123][124][125][130][131][132][133][134][135][136][137][138][139][140], strontium [141,122,127,128,131,140,[142][143][144][145][146][147][148][149][150][151][152][153] and fluoride [64,65,67,69,<...>…”
Section: Improve the Biological Performance Of Calcium Phosphates Witmentioning
confidence: 99%
“…tricalcium phosphate (TCP) [131,147], biphasic calcium phosphate (BCP) [283] and hydroxyapatite (HA) [153]) and subsequently be released when these materials dissolve in aqueous solutions [131,153]. As the Sr substitution of Ca can be obtained in a range varying from 0 to 100 mol % [53], which increases the solubility of the doped apatite [43], a sustained Sr release could be feasible.…”
Section: Introductionmentioning
confidence: 99%